STYLISTIC STUDY: AN ANALYSIS OF THE SELECTED SONGS OF THE S.I.G.I.T - Jati Widya Iswara; Hadziq Najmuddin Purwanto; Fitria Retno Indarsih; Ika Syelvy Rizqyani (Educational Tracker, 2022)
A study of song interpretation becomes an analysis that prominent about how the author's message is conveyed in the lyrics. This study focuses on analyzing and explaining the style of song lyrics as used and it appears in the selected song lyrics of The S. I. G. I. T. Furthermore, this study also showed the importance of each language style in the lyrics. The research method is a descriptive qualitative method using stylistic theory. This study used listening, reading, and note-taking techniques. Writers are therefore an important means of handling secondary data sources carefully, focused, and exhaustively. The results are dominated by casual and intimate linguistic styles. This study found four types of language styles found within the song lyrics namely allegory, metaphor, epic simile, and also sarcasm.